Modern architecture : a critical history - Frampton, Kenneth (London : Thames and Hudson, 1997)
This acclaimed survey of 20th-century architecture and its origins has become a classic since it first appeared in 1980. Now revised, enlarged and expanded, Kenneth Frampton brings the story up to date and adds an entirely new concluding chapter that focuses on four countries where individual talent and enlightened patronage have combined to produce a comprehensive and convincing architectural culture: Finland, France, Spain and Japan.
Pt. I. Cultural developments and predisposing techniques 1750-1939. 1. Cultural transformations: Neo-Classical architecture 1750-1900. 2. Territorial transformations: urban developments 1800-1909. 3. Technical transformations: structural engineering 1775-1939 --
Pt. II. A critical history 1836-1967. 1. News from Nowhere: England 1836-1924. 2. Adler and Sullivan: the Auditorium and the high rise 1886-95. 3. Frank Lloyd Wright and the myth of the Prairie 1890-1916. 4. Structural Rationalism and the influence of Viollet-le-Duc: Gaudi, Horta, Guimard and Berlage 1880-1910. 5. Charles Rennie Mackintosh and the Glasgow School 1896-1916. 6. The Sacred Spring: Wagner, Olbrich and Hoffmann 1886-1912. 7. Antonio Sant'Elia and Futurist architecture 1909-14. 8. Adolf Loos and the crisis of culture 1896-1931. 9. Henry van de Velde and the abstraction of empathy 1895-1914. 10. Tony Garnier and the Industrial City 1899-1918. 11. Auguste Perret: the evolution of Classical Rationalism 1899-1925. 12. The Deutsche Werkbund 1898-1927. 13. The Glass Chain: European architectural Expressionism 1910-25. 14. The Bauhaus: the evolution of an idea 1919-32. 15. The New Objectivity: Germany, Holland and Switzerland 1923-33. 16. De Stijl: the evolution and dissolution of Neo-Plasticism 1917-31. 17. Le Corbusier and the Esprit Nouveau 1907-31. 18. Miesvan der Rohe and the significance of fact 1921-33. 19. The New Collectivity: art and architecture in the Soviet Union 1918-32. 20. Le Corbusier and the Ville Radieuse 1928-46. 21. Frank Lloyd Wright and the Disappearing City 1929-63. 22. Alvar Aalto and the Nordic tradition: National Romanticism and the Doricist sensibility 1895-1957. 23. Giuseppe Terragni and the architecture of Italian Rationalism 1926-43. 24. Architecture and the State: ideology and representation 1914-43. 25. Le Corbusier and the monumentalization of the vernacular 1930-60. 26. Mies van der Rohe and the monumentalization of technique 1933-67. 27. The Eclipse of the New Deal: Buckminster Fuller, Philip Johnson and Louis Kahn 1934-64 --
Pt. III. Critical assessment and extension into the present 1925-91. 1. The International Style: theme and variations 1925-65. 2. New Brutalism and the architecture of the Welfare State: England 1949-59. 3. The vicissitudes of ideology: CIAM and Team X, critique and counter-critique 1928-68. 4. Place, Production and Scenography: international theory and practice since 1962. 5. Critical Regionalism: modern architecture and cultural identity. 6. World architecture and reflective practice.
Str.345-366: Selektirana bibliografija
Kazalo imena
Keywords: moderna arhitektura